2009
DOI: 10.1007/s12307-008-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Molecular Distinctions Between Normal Breast-Associated Fibroblasts and Breast Cancer-Associated Fibroblasts

Abstract: Stromal fibroblasts influence the behavior of breast epithelial cells. Fibroblasts derived from normal breast (NAF) inhibit epithelial growth, whereas fibroblasts from breast carcinomas (CAF) have less growth inhibitory capacity and can promote epithelial growth. We sought to identify molecules that are differentially expressed in NAF versus CAF and potentially responsible for their different growth regulatory abilities. To determine the contribution of soluble molecules to fibroblast–epithelial interactions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 41 publications
(62 reference statements)
1
46
0
Order By: Relevance
“…Thus, in breast cancer, significant differences between CAFs and normal counterparts or CAFs derived from different clinical subtypes have been described previously (21)(22)(23). In nonsmall cell lung cancer, genes relating to the TGF-b signaling pathway are differently expressed by NFs and CAFs (24).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, in breast cancer, significant differences between CAFs and normal counterparts or CAFs derived from different clinical subtypes have been described previously (21)(22)(23). In nonsmall cell lung cancer, genes relating to the TGF-b signaling pathway are differently expressed by NFs and CAFs (24).…”
Section: Discussionmentioning
confidence: 97%
“…To obtain clues as to the stromal pathways involved in CAF-dependent facilitation of malignant phenotypes, several studies have compared gene expression in disease-free fibroblasts and CAFs derived from various tissues (Sadlonova et al 2009;Saadi et al 2010;DeFilippis et al 2012;Berdiel-Acer et al 2014). In one of these studies conducted in breasts, the most dramatic change in expression between disease-free fibroblast and CAF populations was the repression of a cell surface protein, CD36.…”
Section: Cafs and Disease Progressionmentioning
confidence: 99%
“…These genes are implicated in paracrine or intracellular signaling, transcriptional regulation, ECM production and cell adhesion/migration (Bauer et al, 2010). In another study, 420 genes were found to be differentially expressed in CAFs versus NBFs (Sadlonova et al, 2009). Furthermore, 2-Dimentional (2D) gel electrophoresis analysis revealed a great variation in global protein expression between CAFs, NFs and NBFs.…”
Section: Genetic and Epigenetic Changes In Breast Cancerassociated Mymentioning
confidence: 99%
“…These factors are used by activated fibroblasts to communicate with cancer cells as well as with other stromal cells. Microarray and proteomics analysis have revealed distinct mRNA and protein expression profiles in CAFs as compared to their adjacent normal counterparts (NFs) and normal fibroblasts isolated from mammary reduction surgery (NBFs), showing genetic and/or epigenetic alterations in these stromal fibroblasts (Allinen et al, 2004;Bauer et al, 2010;Hawsawi et al, 2008;Sadlonova et al, 2009). Consistent with this, CAFs exhibit some cancer-specific changes, including defective p53/p21-dependent signaling pathway in response to g-rays, high level of survivin, increased resistance to cisplatin and UV light and strong expression of the proliferation markers Ki-67 and PCNA (Hawsawi et al, 2008).…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%